Tourism and Chinese popular nationalism - Cheng, Mingming; Wong, A. (2014)
As a complex and emerging phenomenon, nationalism presents a serious challenge to international marketers, with no exception to the field of tourism. However, there is a lack of empirical evidence in understanding the role of nationalism in tourist travel intention. A qualitative research approach with in-depth interview and on-site observation was adopted to bridge this gap during the Diaoyu/Senkaku Island Incident between China and Japan since late 2012. In particular, this study seeks to shed light on the influence of nationalism on Chinese tourists. A nationalism dynamics model has been established to explore and explain different segments of tourists based on their self-perceived level of nationalism. The findings of this paper offer important implications for both scholars and practitioners in their strategic responses to this challenging nationalism phenomenon.